Self-talk intervention using video-imagery: effects on under 19 state soccer players - Thariq Khan Azizuddin Khan (Tanjong Malim, 2019)
Self-talk intervention using video-imagery: effects on under 19 state soccer players by Thariq Khan Azizuddin Khan